FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHASILAN USAHA SALON DI KOTA SOLO - -, Suwarto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
This study aims to analyze (1) Effect of products on the income of salon business in the city of Solo, (2) The effect of price on the income of salon business in the city of Solo, (3) Effect of promotions on the income of salon business in the city of Solo. This study is a sample research with 35 respondents of salon entrepreneur in the city of Solo, using proporsional sample random sampling. To test the hypothesis, researcher used linear multiple regression analysis, data processing using SPSS. The results of this study point to the fact (1) Product services significantly influence the salon business income in the city of Solo, indicated by p value of 0.02, so the hypothesis 1 is proved. (2) Price significant effect on the income of salon business in the city of Solo, indicated by p value of 0.024, so the hypothesis 2 is proved. (3) Promotion of a significant effect on operating income in the city of Solo salon indicated by p value of 0.030, so the hypothesis 3 is proved.Keywords: income, service, products, price, promote